An implantable sensor based on multi-layer cross-linked polymer outer membrane modification, preparation method and application

CN122983162APending Publication Date: 2026-10-27ZHEJIANG POCTECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611453290.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]但是现有的外膜能够阻隔的干扰物种类有限,传感器的监测准确度仍然有待提升,另外,外膜的稳定性差,传感器植入人体长期使用过程中,外膜容易发生溶胀,甚至剥离,从而导致传感器功能受损或者完全失效,无法实现长期稳定的监测

Benefits of technology

本申请通过将功能性聚合物溶于乙醇-HEPES缓冲溶液中得到的功能性聚合物溶液浸泡预处理传感器,功能性聚合物溶液形成包覆主体外膜的功能外膜,在主体外膜外附着功能外膜使得外膜能够阻隔更多种类的干扰物,提升了传感器的监测准确度。另外,利用乙醇-HEPES缓冲溶液对主体外膜进行浸泡处理,使得主体外膜部分溶胀、溶解,促进两种聚合物链的交叉缠结,利于两种膜的融合,减少了不同聚合物层间分离的概率,从而将主体外膜和功能外膜牢固地附着到感测层,使植入式传感器在长期工作环境下能够保持结构和功能的稳定,确保传感器在整个佩戴过程中的监测准确度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122983162A_ABST
    Figure CN122983162A_ABST
Patent Text Reader

Abstract

The application provides an implantable sensor based on a multilayer cross-linked polymer outer film modification, a preparation method and application, and relates to the technical field of electrochemical detection. The preparation method of the implantable sensor based on the multilayer cross-linked polymer outer film modification comprises the following steps: after a sensor with a prepared main body outer film is soaked and treated in an ethanol-HEPES buffer solution, the sensor is soaked and treated in a functional polymer solution. The sensor is prepared through the pre-soaking treatment of the main body outer film and the soaking treatment in the functional polymer solution, firm interface combination between the multilayer films is realized, the separation between the layers of different polymers is reduced, the detection precision and reliability of the implantable sensor are improved, the sensor can maintain excellent performance in a long-term working environment, and the defects of the existing implantable sensor are made up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical detection technology, and in particular to an implantable sensor based on a multilayer cross-linked polymer outer membrane, its preparation method, and its application. Background Technology

[0002] With the development of medical technology, continuous analyte monitoring devices that can continuously monitor users' health indicators have gradually appeared on the market. These devices can generate electrical signals by reacting with analytes in interstitial fluid through the biosensor layer implanted under the skin. The electrical signals are then converted into analyte data and transmitted wirelessly to a display terminal via a transmitter to achieve continuous monitoring of users' analytes.

[0003] Although the biosensor layer exhibits high reaction specificity, the interstitial fluid of human tissue contains a large number of endogenous electrochemically active substances. These substances readily undergo redox reactions under the sensor's operating voltage, severely interfering with the detection results of the target analyte and significantly reducing monitoring accuracy. Coating the surface of the sensing layer with an outer membrane to reduce the transmittance of interfering substances through sieving and blocking can, to some extent, reduce stray signal interference and improve the sensor's monitoring accuracy.

[0004] However, existing outer membranes can only block a limited variety of interfering substances, and the monitoring accuracy of sensors still needs improvement. Furthermore, the outer membrane has poor stability; during long-term use after implantation, it is prone to swelling or even peeling, leading to sensor damage or complete failure, thus hindering long-term stable monitoring. Therefore, developing an implantable sensor that balances high anti-interference capabilities with long-term functional stability is a pressing technical problem that needs to be solved in this field. Summary of the Invention

[0005] The purpose of this application is to address the shortcomings of existing technologies by providing an implantable sensor based on a multilayer cross-linked polymer outer membrane, its preparation method, and its application.

[0006] To achieve the above objectives, the technical solution adopted in this application is as follows: According to one aspect of this application, a method for fabricating an implantable sensor based on a multilayer cross-linked polymer outer membrane modification is provided, comprising the following steps: A main outer film is formed on the sensing layer of the sensor; The sensor with the prepared outer membrane is immersed in an ethanol-HEPES buffer solution, then removed to obtain a pretreated sensor. The functional polymer was dissolved in an ethanol-HEPES buffer solution, a crosslinking agent was added and stirred until homogeneous, and then filtered to obtain a functional polymer solution. The pretreated sensor was immersed in a functional polymer solution, then removed and air-dried.

[0007] Currently, the main method for preparing multilayer membrane structure sensors involves directly coating a functional outer membrane solution containing a crosslinking agent onto the first outer membrane, followed by solvent evaporation / crosslinking reaction, and drying to form a new functional outer membrane shell. However, this method results in significant boundaries between the multilayer membranes and poor interfacial bonding. This means that during long-term operation in bodily fluid environments, the functional outer membrane swells along with the main outer membrane and itself, often leading to increased intermembrane boundaries and even the risk of detachment or peeling, thus compromising the expected performance and hindering the long-term, accurate operation of the sensor.

[0008] This application employs the above method to first pretreat the outer membrane of the main body using an ethanol-HEPES buffer solution, causing the outer membrane shell to swell or partially dissolve, thereby breaking down the dense solid aggregates and freeing up crosslinkable sites. Then, it is immersed in a functional polymer solution, allowing polymer chain entanglement and crosslinking reactions between polymer chains to occur during the subsequent solvent evaporation process, improving the interfacial bonding between the multilayer membranes. This enhances the detection accuracy and reliability of the implantable sensor and ensures that the sensor maintains excellent performance under long-term working conditions, thus overcoming the shortcomings of existing implantable sensors.

[0009] It should be noted that in the above-mentioned method for preparing implantable sensors based on multilayer cross-linked polymer outer membrane modification, the functional polymer solution preparation step can be performed before or after the main outer membrane formation step, or it can be performed simultaneously with the main outer membrane formation step, without any special limitation.

[0010] Furthermore, in the ethanol-HEPES buffer solution, the volume ratio of ethanol to HEPES buffer solution is (4-5):1.

[0011] Furthermore, the main outer membrane is formed from a main outer membrane polymer obtained by reacting poly(4-vinylpyridine-co-4-styrene) with 1,3-propanesulfonate lactone; wherein, In poly(4-vinylpyridine-co-4-styrene), the molar ratio of the structural unit 4-vinylpyridine to 4-styrene is (80-95):10, for example, it can be 80:10, 81:10, 82:10, 83:10, 84:10, 85:10, 86:10, 87:10, 88:10, 89:10, 90:10, 91:10, 92:10, 93:10, 94:10, 95:10 or any range between them, preferably (85-95):10, more preferably 90:10; Based on the structural unit 4-vinylpyridine in poly(4-vinylpyridine-co-4-styrene), the molar ratio of 4-vinylpyridine to 1,3-propanesulfonic acid lactone is (5-20):1, preferably (8-15):1, and more preferably 10:1.

[0012] Furthermore, the preparation method of the main outer membrane polymer includes the following steps: Poly(4-vinylpyridine-co-4-styrene) was added to a three-necked round-bottom flask, and then anhydrous N,N-dimethylformamide was added and dissolved completely. 1,3-propanesulfonic acid lactone was dissolved completely in N,N-dimethylformamide and then slowly added dropwise to the polymer solution at room temperature, and stirred for 30 min. After purging with nitrogen three times, the reaction was carried out at 60 °C for 15–18 h. After the reaction was completed, the reaction solution was cooled to room temperature, anhydrous ethanol was added, and the mixture was filtered. The filtrate was added dropwise to deionized water stirred with a stir bar to settle, and the white solid on the stir bar was collected and cut into small pieces. The filtrate was dissolved again in ethanol and added dropwise to deionized water stirred with a stir bar to settle, and the white solid on the stir bar was collected and cut into small pieces. The mixture was dried in a forced-air drying oven for 72 h to obtain the final product. The reaction formula is shown in formula (I) below. (I); Furthermore, the specific steps for forming the main outer membrane on the sensing layer of the sensor are as follows: dissolve the main outer membrane polymer in an ethanol-HEPES buffer solution containing a crosslinking agent, with a volume ratio of ethanol to HEPES buffer solution of (4-5):1; the concentration of the crosslinking agent is 4-5 mg / mL; and obtain the sensor with the prepared main outer membrane by 9-11 immersion-lifting cycles of the working electrode with the enzyme sensing layer formed.

[0013] Furthermore, the crosslinking agent is polyethylene glycol diglycidyl ether.

[0014] Furthermore, the total thickness of the outer membrane of the main body is 35–45 μm.

[0015] Furthermore, the sensor with the prepared outer membrane is immersed in the ethanol-HEPES buffer solution for 5 to 20 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes or any range thereof, preferably 10 to 15 minutes, more preferably 10 minutes.

[0016] This application utilizes an ethanol-HEPES buffer solution to immerse the outer membrane of the main body, which ensures that the swelling and partial dissolution of the polymer in the outer membrane are completed during the immersion process. This breaks up the solid aggregation of polymer chains and exposes the cross-linking sites on the polymer chains, which is beneficial for the fusion of the two membranes after the functional outer membrane is coated, thereby obtaining a sensor with stable structure and function.

[0017] The immersion time directly affects the structure of the outer membrane and thus the performance of the sensor. Studies have found that insufficient immersion time cannot guarantee a strong bond between the multilayer membranes, resulting in poor long-term stability of the sensor; while excessive immersion time, although ensuring long-term stability, does not significantly improve detection accuracy and reliability. This application controls the immersion time to 5–20 minutes, with 10 minutes being particularly effective in achieving optimal stability and accuracy of monitoring results.

[0018] Furthermore, the functional polymer is obtained by copolymerizing sodium 4-vinylbenzenesulfonate with 4-vinylpyridine; The functional polymer contains 5-45% sodium 4-vinylbenzenesulfonate, preferably 10-30%, and more preferably 15%.

[0019] Furthermore, the method for preparing the functional polymer includes the following steps: Sodium 4-vinylbenzenesulfonate was added to a three-necked round-bottom flask and dissolved completely in deionized water. An initiator was added to the system and dissolved completely. 4-vinylpyridine and anhydrous ethanol were added to the system. After purging with nitrogen three times, the system was sonicated to promote dissolution. After purging with nitrogen five times, the system was reacted at 70°C for 22–25 h. After the reaction was completed, the reaction solution was cooled to room temperature, filtered, and the filtrate was collected. The filtrate was slowly added dropwise to ethyl acetate under stirring to settle, filtered, and the white solid was collected. The solid was then dissolved again in ethanol and slowly added dropwise to ethyl acetate under stirring to settle, filtered, and dried to obtain the final product. The reaction formula is shown in formula (II) below. (II); The initiator is a conventional initiator in the field, such as a peroxide initiator, and the amount of peroxide initiator is 0.1 to 0.5% of the total molar amount of sodium 4-vinylbenzenesulfonate and 4-vinylpyridine.

[0020] The weight-average molecular weight of the functional polymer is 300,000 to 1,000,000.

[0021] Furthermore, the crosslinking agent is polyethylene glycol diglycidyl ether.

[0022] Furthermore, the concentration of the functional polymer in the functional polymer solution is 55–65 mg / mL, and the concentration of the crosslinking agent is 4–6 mg / mL.

[0023] Furthermore, the soaking time in the functional polymer solution is 3 to 9 seconds, preferably 5 to 9 seconds, more preferably 5 to 7 seconds, and even more preferably 5 seconds.

[0024] The functional outer membrane formed by the above-mentioned functional polymers can block the transmission of various interfering substances such as ascorbic acid, acetaminophen, uric acid, and salicylic acid, thereby improving the accuracy and reliability of sensor monitoring results. It can also be replaced with other negatively charged polymers.

[0025] Traditional coating methods involve directly dipping the sensor into the functional outer membrane solution (i.e., without immersion in the solution). In the sensor coating preparation of this application, the sensor is immersed in the functional outer membrane solution for a certain period. The swelling and partial dissolution effects of the outer membrane solution on the existing main outer membrane structure disrupt parts of the existing film shell, causing the film-forming polymer chains to disintegrate and aggregate, exposing crosslinkable sites. During the drying process of the new membrane solution, the polymer chains become entangled with the co-functional polymer chains, and crosslinking reactions occur at the crosslinking sites, forming a gradually changing, boundary-free integral membrane structure. This improves the crosslinking fusion between the functional outer membrane and the main outer membrane, enhancing adhesion. However, as the immersion pretreatment time is further increased, the sensor's anti-interference performance does not continue to improve, while the sensor's response time increases, which is detrimental to the sensor's overall performance.

[0026] Furthermore, the drying conditions are as follows: dry for 18 to 24 hours at 25–30°C and 30–40% humidity.

[0027] Furthermore, after drying, post-treatment is carried out under the following conditions: 48 hours at a temperature of 60℃ and a humidity of 10%.

[0028] Furthermore, the pre-treated sensor membrane increased in thickness by 2–3 μm after immersion in a functional polymer solution.

[0029] According to another aspect of this application, an implantable sensor is provided, comprising: Base; A working electrode is disposed on one side of the substrate; The sensing layer at least partially covers the working electrode; The main outer film covering the sensing layer; and A functional outer membrane covering the outer membrane of the main body; The functional outer membrane is prepared from the functional polymer solution, and the main outer membrane and the functional outer membrane are attached to the sensing layer using the preparation method described above.

[0030] Furthermore, the working electrode can be a carbon-printed electrode or other electrodes well known in the art, and the enzyme sensing layer is formed on the surface of the working electrode by cross-linking and solidifying an enzyme well known to those skilled in the art, such as glucose oxidase (GOx).

[0031] Optionally, the substrate is a substrate well known to those skilled in the art or made from components well known in the art. In one form, the substrate component comprises a thin film of insulating (e.g., electrically insulating and / or waterproof) material, which can be made of various materials having desired properties (e.g., dielectric properties, waterproofness, and hermeticity), such as metal and / or ceramic and / or polymer substrates.

[0032] Furthermore, the implantable sensor based on a multilayer cross-linked polymer outer membrane modification also includes a reference electrode and a counter electrode.

[0033] According to another aspect of this application, an application of the aforementioned implantable sensor is provided, including using the implantable sensor to monitor glucose in interstitial fluid within the body.

[0034] Compared with the prior art, this application has the following beneficial effects: This application pre-treats the sensor by immersing it in a functional polymer solution obtained by dissolving a functional polymer in an ethanol-HEPES buffer solution. This functional polymer solution forms a functional outer membrane covering the main body's outer membrane. The attachment of this functional outer membrane to the main body's outer membrane allows it to block a wider variety of interfering substances, improving the sensor's monitoring accuracy. Furthermore, immersing the main body's outer membrane in the ethanol-HEPES buffer solution causes partial swelling and dissolution, promoting the cross-entanglement of the two polymer chains and facilitating the fusion of the two membranes. This reduces the probability of separation between different polymer layers, thus firmly attaching the main body's outer membrane and the functional outer membrane to the sensing layer. This ensures the implantable sensor maintains structural and functional stability under long-term operating conditions, guaranteeing the sensor's monitoring accuracy throughout the entire wearing process. Attached Figure Description

[0035] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 The above is the 1H NMR spectrum of the main polymer in Example 1 of this application; Figure 2 The above is the 1H NMR spectrum of the functional polymer in Example 1 of this application; Figure 3 This is a microscopic schematic diagram of the cross-linking between the outer membrane layer and the functional membrane layer in Comparative Example 1 and Example 1 of this application; Figure 4 This is a flowchart illustrating the fabrication process of the implantable sensor based on a multilayer cross-linked polymer outer membrane modified according to Example 1 of this application. Figure 5 This is a flowchart illustrating the fabrication process of the implantable sensor based on a multilayer cross-linked polymer outer membrane modified according to Comparative Example 1 of this application. Figure 6This is a schematic diagram showing the test results of the anti-interference performance of the implantable sensor modified with the multilayer cross-linked polymer outer membrane obtained in Comparative Example 1 and Example 1 of this application against sodium ascorbate. Figure 7 This is a schematic diagram showing the test results of the anti-interference performance of the implantable sensor modified with the multilayer cross-linked polymer outer membrane obtained in Comparative Example 2 and Example 2 of this application against sodium ascorbate. Figure 8 This is a schematic diagram of the response time test results of the implantable sensor modified with a multilayer cross-linked polymer outer membrane obtained in Example 2 of this application; Figure 9 This is a schematic diagram showing the test results of the anti-interference performance of the implantable sensor modified with the multilayer cross-linked polymer outer membrane obtained in Comparative Examples 1 and 2 of this application at different time points against sodium ascorbate. Detailed Implementation

[0036] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of this application, but do not limit this application in any way. The following content is merely an exemplary description of the scope of protection claimed in this application, and those skilled in the art can make various changes and modifications to the invention based on the disclosed content, which should also fall within the scope of protection claimed in this application.

[0037] Unless otherwise specified, all chemical reagents used in the embodiments of this application are obtained through conventional commercial means. The application will be further described below by way of specific embodiments.

[0038] Example 1 A method for fabricating an implantable sensor based on a multilayer cross-linked polymer outer membrane modification includes the following steps: The main outer membrane polymer was dissolved in an ethanol-HEPES buffer solution containing a crosslinking agent, with a volume ratio of ethanol to HEPES buffer solution of 4:1; the concentration of the crosslinking agent polyethylene glycol diglycidyl ether (i.e., the concentration in the ethanol-HEPES buffer solution) was 5 mg / mL; the working electrode with the prepared enzyme sensing layer was subjected to 9 dip-pull cycles to obtain the sensor with the prepared main outer membrane.

[0039] The main outer membrane polymer was prepared by the following method: 10.00 g of poly(4-vinylpyridine-co-4-styrene) was added to a three-necked round-bottom flask, followed by the addition of anhydrous N,N-dimethylformamide (100 mL) to dissolve it completely. 1,3-propanesulfonic acid lactone (1.16 g) was dissolved completely in N,N-dimethylformamide (20 mL), and then slowly added dropwise to the polymer solution at room temperature, stirring for 30 min. After three nitrogen purgings, the reaction was carried out at 60 °C for 15 h. After the reaction was complete, the reaction solution was cooled to room temperature, and anhydrous ethanol (20 mL) was added and filtered. The filtrate was added dropwise to deionized water stirred with a stir bar to settle, and the white solid on the stir bar was collected and cut into small pieces with scissors. The solid was then dissolved again in ethanol and added dropwise to deionized water stirred with a stir bar to settle, and the white solid on the stir bar was collected and cut into small pieces with scissors. The mixture was dried in a forced-air drying oven for 72 h to obtain the final product. The 1H NMR spectrum of this functional polymer was measured using a 400MHz NMR spectrometer, as shown below: 1 ¹H NMR (400 MHz, d6-DMSO) δ ppm: 8.815 (s, 1.17 H), 8.252 (s, 9.39 H), 7.443 (s, 1.14 H), 6.84 (m, 12.54 H), 4.658 (m, 1.00 H), 1.88 (m, 18.01 H). See [reference needed]. Figure 1 .

[0040] The sensor with the prepared outer membrane is immersed in an ethanol-HEPES buffer solution (volume ratio of ethanol to HEPES buffer solution is 4:1) for 5-20 minutes, then removed to obtain a pretreated sensor.

[0041] The functional polymer was dissolved in an ethanol-HEPES buffer solution (volume ratio of ethanol to HEPES buffer solution was 4:1) at a concentration of 60 mg / mL. Polyethylene glycol diglycidyl ether was added at a concentration of 5 mg / mL and stirred until homogeneous. The mixture was then filtered to obtain the functional polymer solution. Functional polymers are prepared by the following method: Sodium 4-vinylbenzenesulfonate (6.92 g) was added to a 500 mL three-necked round-bottom flask and dissolved completely in 30 mL of deionized water. Potassium persulfate (300 mg) was added and dissolved completely. 4-Vinylpyridine (20 g) and 200 mL of anhydrous ethanol were added. After purging with nitrogen three times, the mixture was sonicated to promote dissolution. After purging with nitrogen five times, the mixture was reacted at 70 °C for 24 h. After the reaction was complete, the mixture was cooled to room temperature, diluted with 300 mL of ethanol, filtered through a 0.22 μm nylon membrane, and the filtrate was collected. The filtrate was distilled under reduced pressure to approximately 100 mL, and ethanol was added to bring the volume to 300 mL. The mixture was then concentrated again under reduced pressure to approximately 100 mL. The ethanol solution was brought to a final volume of 250 mL and slowly added dropwise to 2 L of ethyl acetate under stirring until precipitation. The mixture was filtered through filter paper, and the white solid was collected. The white solid was redissolved in 250 mL of ethanol and slowly added dropwise to 2 L of ethyl acetate under stirring until precipitation. The mixture was filtered through filter paper, and the white solid was collected. After drying the solid overnight at room temperature in an evaporating dish, it was then dried under reduced pressure at room temperature in a vacuum oven for three days to obtain a white powdery solid, which is the functional polymer. The 1H NMR spectrum of this functional polymer, measured using a 400MHz NMR spectrometer, is as follows: 1 ¹H NMR (400 MHz, d6-DMSO) δ ppm: 8.245 (m, 0.85 H), 7.452 (s, 0.15 H), 6.590 (s, 1H), 3.486 (m, 0.55H), 1.532 (m, 1.33H). The ¹H NMR spectrum is shown below. Figure 2 The functional polymer has a weight-average molecular weight of 381,000 and a molecular weight distribution index of 1.21.

[0042] The pretreated sensor was immersed in a functional polymer solution for 5 seconds, then pulled out of the solution and air-dried at room temperature. It was then treated at 25°C and 40% humidity for 24 hours, and finally treated at 60°C and 10% humidity for 48 hours to obtain an implantable sensor modified with a multi-layer cross-linked polymer outer membrane.

[0043] The fabrication process of the implantable sensor based on the multilayer cross-linked polymer outer membrane modification is as follows: Figure 4 As shown.

[0044] In the implantable sensor modified with the obtained multilayer cross-linked polymer outer membrane, the cross-linking microstructure between the main outer membrane and the functional outer membrane is as follows: Figure 3As shown in (b), the thick solid lines represent the main outer membrane polymer chains, the thick dashed lines represent the functional polymer chains, and the thin curves represent the crosslinking agents. It can be seen that after pretreatment with the ethanol / HEPES solution, the rigid structure of the main outer membrane partially swells, dissolves, and deaggregates to create crosslinkable sites, which facilitates the interaction with the functional outer membrane in the subsequent S4 step. The main outer membrane polymer chains and the functional polymer chains achieve crosslinking and fusion, forming a gradually transitioning, boundary-free integral membrane structure, i.e., a fusion layer. There is no obvious boundary between the main outer membrane and the functional outer membrane, thus ensuring a strong bond between the multilayer membranes and improving the long-term operational stability of the sensor.

[0045] Following the steps described above, this embodiment prepared a series of implantable sensors modified with multilayer cross-linked polymer outer membranes. The difference lies in the soaking time of the prepared sensor outer membrane in ethanol-HEPES buffer solution. The specific soaking time is shown in Table 1 below.

[0046] Table 1

[0047] Example 2 A method for fabricating an implantable sensor based on a multilayer cross-linked polymer outer membrane modification includes the following steps: The main outer membrane polymer was dissolved in an ethanol-HEPES buffer solution containing a crosslinking agent, with a volume ratio of ethanol to HEPES buffer solution of 4:1; the concentration of the crosslinking agent polyethylene glycol diglycidyl ether was 5 mg / mL; the working electrode with the prepared enzyme sensing layer was subjected to 9 dip-pull cycles to obtain the sensor with the prepared main outer membrane.

[0048] The sensor with the prepared outer membrane was immersed in an ethanol-HEPES buffer solution (the volume ratio of ethanol to HEPES buffer solution was 4:1) for 10 minutes, and then removed to obtain the pretreated sensor.

[0049] The functional polymer was dissolved in an ethanol-HEPES buffer solution (volume ratio of ethanol to HEPES buffer solution was 4:1) at a concentration of 60 mg / mL. Polyethylene glycol diglycidyl ether was added at a concentration of 5 mg / mL and stirred until homogeneous. The mixture was then filtered to obtain the functional polymer solution. The preparation method of the functional polymer is the same as in Example 1.

[0050] The pretreated sensor is immersed in a functional polymer solution for 3-9 seconds, then pulled out of the solution and air-dried at room temperature. It is then placed at 25°C and 40% humidity for 24 hours, and finally treated at 60°C and 10% humidity for 48 hours to obtain an implantable sensor modified with a multi-layer cross-linked polymer outer membrane.

[0051] Following the steps described above, this embodiment prepared a series of implantable sensors modified with multilayer cross-linked polymer outer membranes. The difference lies in the different soaking times of the pre-treated sensors in the functional polymer solution in step S4. The specific soaking times are shown in Table 2 below.

[0052] Table 2

[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that the sensor with the prepared outer membrane was not immersed in the ethanol-HEPES buffer solution, but directly immersed in the functional polymer solution for 5 seconds, then pulled out of the solution and air-dried. The preparation process of the implantable sensor based on the multilayer cross-linked polymer outer membrane modification is as follows: Figure 5 As shown.

[0054] In the implantable sensor modified with the obtained multilayer cross-linked polymer outer membrane, the cross-linking microstructure between the main outer membrane and the functional outer membrane is as follows: Figure 3 As shown in (a), the thick solid lines represent the polymer chains of the main outer membrane, the thick dashed lines represent the functional polymer chains, and the thin curves represent the crosslinking agents. It can be seen that there is a clear boundary between the main outer membrane and the functional outer membrane.

[0055] Comparative Example 2 The difference between this comparative example and Example 2 is that the pre-treated sensor was dipped directly into the functional polymer solution and then immediately pulled out of the solution.

[0056] Test Example 1 The implantable sensors modified with multilayer cross-linked polymer outer membranes obtained in Example 1 and Comparative Example 1 were tested for their anti-interference performance against sodium ascorbate. The glucose solution concentration was 13.9 mM. The interference deviation was calculated as follows: the stable current without sodium ascorbate was recorded as I0; the stable current reached again after adding sodium ascorbate was recorded as I... Vc Interference bias = (I Vc – I0) / I0 × 100%.

[0057] Test results are available Figure 6 .

[0058] like Figure 6As shown, sensors treated with different soaking pretreatment times exhibited different anti-interference performance against ascorbic acid. In the figure, (a) represents the sensor with the prepared outer membrane in Example 1, (b) represents Comparative Example 1, and (c) to (f) represent Examples 1-1 to 1-4, respectively. In Comparative Example 1, the outer membrane was not soaked, and the sensor exhibited the worst anti-interference performance against ascorbic acid, with the largest deviation in current occurring upon the addition of ascorbic acid. As the soaking pretreatment time increased, the deviation of the sensor current upon the addition of ascorbic acid first decreased and then slightly increased. When the soaking pretreatment time was 10 min, the sensor current was least affected by ascorbic acid; however, all soaked sensors still performed better than the untreated sensors.

[0059] Therefore, the immersion pretreatment time directly affects the fine structure of the polymer in the main outer membrane layer. This study found that immersion pretreatment within 5-20 minutes can complete the swelling and partial dissolution of the polymer in the main outer membrane, breaking down the solid aggregates of the polymer chains and exposing the cross-linking sites on the polymer chains. This facilitates the fusion of the two membranes after the second functional outer membrane is coated, resulting in a sensor with stable structure and interference resistance. Immersion in the pretreatment solution for 10 minutes yields the best performance. Further increases in immersion pretreatment time do not lead to further improvement in the sensor's interference resistance.

[0060] Test Example 2 The implantable sensor modified with the multilayer cross-linked polymer outer membrane obtained in Comparative Example 2 and Example 2 was tested for its anti-interference performance against sodium ascorbate.

[0061] Test results are available Figure 7 .

[0062] like Figure 7 As shown, sensors obtained by immersion in functional polymer solutions for different treatment times exhibit different anti-interference performance against ascorbic acid. In the figure, (a) represents Comparative Example 2, and (b) to (e) represent Examples 2-1 to 2-4, respectively. All sensors showed anti-interference performance against ascorbic acid, but in Comparative Example 2, the sensors were only dipped into the functional polymer solution without immersion treatment, resulting in poor anti-interference performance against ascorbic acid, and the current still showed some deviation when ascorbic acid was added. As the immersion time in the functional polymer solution increased, the deviation of the sensor current when ascorbic acid was added decreased. When the immersion pretreatment time was 5s, the sensor current was less affected by ascorbic acid and the increase in sensor response time was not significant; however, all immersion-treated sensors still performed better than the untreated sensors.

[0063] Therefore, the immersion time in the functional polymer solution affects the fine structure of the fused layer between the main outer membrane and the functional outer membrane. This study found that immersion within 9 seconds allows for the interaction between the polymer chains of the main outer membrane and the functional polymer chains, facilitating the fusion of the two membranes after the second functional outer membrane is coated. This results in a sensor with stable structure and interference resistance, but with some differences in response time. Immersion for 5 seconds yields the sensor with the best overall performance. Further increases in immersion time do not improve the sensor's interference resistance, but instead prolong the response time.

[0064] Test Example 3 The performance of the implantable sensors modified with multilayer cross-linked polymer outer membranes obtained in Examples 2-1 to 2-4 was tested in different glucose solutions. The test results are shown in [the table below]. Figure 8 .

[0065] Figure 8 In the examples, (a) to (d) represent Examples 2-1 to 2-4, respectively. During the testing process, several sensors were used simultaneously for each example. Sensors with different soaking times were placed in glucose solutions and their currents were measured. After the current reached a stable plateau and remained so for a period of time, a higher concentration of glucose solution was added. Figure 8 As can be seen, the longer the immersion time, the longer it takes for the sensor current to reach a stable plateau. Taking the example of placing the sensor in a 5 mmol / L glucose solution until it reaches a stable plateau, and then quickly switching to a 10 mmol / L glucose solution, the sensor response time is shortest after immersion for 3 seconds, at 200-240 seconds; the sensor response time is longest after immersion for 9 seconds, reaching 270-290 seconds.

[0066] Test Example 4 The anti-interference performance of the sensors in Comparative Example 1 and Examples 2-2 against sodium ascorbate was tested after operating in solution for 0, 10, and 15 days. The results are shown in [Figure Number]. Figure 9 .

[0067] Figure 9 In the diagram, (a) to (c) represent the anti-interference performance of the sensor in Comparative Example 1 after 0, 10, and 15 days of operation, respectively, and (d) to (f) represent the anti-interference performance of the sensors in Examples 2-2 after 0, 10, and 15 days of operation, respectively. Figure 9As shown, Example 2-2 exhibited a smaller interference deviation value compared to the sensor in Comparative Example 1 at all time points, demonstrating better anti-interference performance. The interference deviation value of Example 2-2 increased slightly at three time points, ultimately maintaining a maximum deviation within 6% in the presence of 60 mg / mL sodium ascorbate. The Comparative Example showed limited anti-interference performance at day 0, which further decreased with increasing operating time; after 10 days of operation, its anti-interference performance was almost completely lost, with an interference deviation of nearly 20% in 60 mg / mL sodium ascorbate, similar to the interference deviation of the sensor without the anti-interference functional polymer layer.

[0068] Therefore, the immersion treatment of the outer membrane and the immersion treatment in the functional polymer solution are particularly important for maintaining the long-term stability of the sensor's anti-interference performance. In other words, the multilayer membrane sensor prepared by this invention can maintain structural stability over a long period. The immersion pretreatment and the treatment in the functional polymer solution greatly alleviate the separation tendency between the multilayer polymer membranes, promoting the physical (entanglement) and chemical (crosslinking reaction) fusion between different polymers. This is ultimately verified by comparing the sensor's anti-interference performance at different time points.

[0069] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles of the monitoring methods described herein can be applied to other embodiments without inventive effort. Therefore, this application is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of this application without departing from the scope of this application should be within the protection scope of this application.

Claims

1. A method for fabricating an implantable sensor based on a multilayer cross-linked polymer outer membrane modification, characterized in that, Includes the following steps: A main outer film is formed on the sensing layer of the sensor; The sensor with the prepared outer membrane is immersed in an ethanol-HEPES buffer solution for 5–20 minutes, then removed to obtain a pretreated sensor. The functional polymer was dissolved in an ethanol-HEPES buffer solution, a crosslinking agent was added and stirred until homogeneous, and then filtered to obtain a functional polymer solution. Immerse the pretreated sensor in a functional polymer solution for 3–9 seconds, then remove and air dry.

2. The preparation method according to claim 1, characterized in that, In the ethanol-HEPES buffer solution, the volume ratio of ethanol to HEPES buffer solution is (4-5):

1.

3. The preparation method according to claim 1, characterized in that, The functional polymer is obtained by copolymerizing sodium 4-vinylbenzenesulfonate with 4-vinylpyridine.

4. The preparation method according to claim 3, characterized in that, The molar ratio of sodium 4-vinylbenzenesulfonate in the functional polymer is 5-45%.

5. The preparation method according to claim 1, characterized in that, In the functional polymer solution, the concentration of the functional polymer is 55–65 mg / mL, and the concentration of the crosslinking agent is 4–6 mg / mL.

6. The preparation method according to claim 1, characterized in that, After drying, post-treatment is carried out under the following conditions: 60℃ and 10% humidity for 48 hours.

7. An implantable sensor, characterized in that, include: Base; A working electrode is disposed on one side of the substrate; The sensing layer at least partially covers the working electrode; The main outer film covering the sensing layer; as well as A functional outer membrane covering the outer membrane of the main body; The functional outer membrane is prepared from the functional polymer solution, and the main outer membrane and the functional outer membrane are attached to the sensing layer using the preparation method described in any one of claims 1-6.

8. The implantable sensor according to claim 7, characterized in that, It also includes a reference electrode and a counter electrode.

9. The application of the implantable sensor according to claim 7 or 8, characterized in that, This includes using the implanted sensor to monitor glucose in the interstitial fluid within the body.